2012
DOI: 10.1007/s12024-012-9402-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful direct amplification of nuclear markers from a single hair follicle

Abstract: We report on successful amplification of DNA profiles from a single hair. Direct amplification was used on the root tip of both anagen and telogen hairs using a kit to amplify 15 STR loci. All 30 anagen hairs tested from five different people gave full DNA profiles after 29 cycles with no allelic drop-in or heterozygous imbalance. Six of the 30 telogen hairs tested resulted in a full DNA profile, and a further four telogen hair samples tested produced a DNA profile of five or more complete loci that could be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Hair growth and development has been studied by developmental biologists, geneticists, and dermatologists (Bernard, 2016;Fuchs et al, 2001;Kaplan & Holbrook, 1994;Legué, Sequeira, & Nicolas, 2010). Occasionally the term "hair follicle" has been inaccurately interchanged with the bulbous proximal end of a hair otherwise known as the "hair root" (Haines & Linacre, 2016;Ottens, Taylor, Abarno, & Linacre, 2013). The hair follicle is the organ from which the hair grows and remains in the scalp when a hair shaft is pulled or shed, while the root is the bulbous portion of the hair shaft that resides in the follicle until the hair is shed or pulled (Bassukas & Hornstein, 1989;Langbein et al, 2002).…”
Section: Growth Stagesmentioning
confidence: 99%
“…Hair growth and development has been studied by developmental biologists, geneticists, and dermatologists (Bernard, 2016;Fuchs et al, 2001;Kaplan & Holbrook, 1994;Legué, Sequeira, & Nicolas, 2010). Occasionally the term "hair follicle" has been inaccurately interchanged with the bulbous proximal end of a hair otherwise known as the "hair root" (Haines & Linacre, 2016;Ottens, Taylor, Abarno, & Linacre, 2013). The hair follicle is the organ from which the hair grows and remains in the scalp when a hair shaft is pulled or shed, while the root is the bulbous portion of the hair shaft that resides in the follicle until the hair is shed or pulled (Bassukas & Hornstein, 1989;Langbein et al, 2002).…”
Section: Growth Stagesmentioning
confidence: 99%
“…Studies implementing direct PCR methods on single fibres and touch DNA samples also indicate that the likely source of DNA, nucleated, or cell‐free, is present on the surface of the sample . Studies into direct PCR of human hairs showed an increased success rate compared to methods that use a DNA extraction step . The aim of this study was to demonstrate the success rate of nuclear DNA recovery from single dog hairs that represent forensic casework scenarios thus allowing routine STR typing of a single shed hair.…”
Section: Sample Breakdown Of the Type Of Hair Used Per Sample Collectmentioning
confidence: 98%
“…Naturally shed hairs are the most commonly found hair types at crimes scenes. These telogen hairs have finished the growth cycle and lack the sheathing and root bulb, which typically contain high amounts of nuclear DNA required for successful profiling . Mitochondrial DNA (mtDNA) has a much higher copy number within cells, which has made it the primary focus of DNA analysis involving the domestic dog .…”
Section: Sample Breakdown Of the Type Of Hair Used Per Sample Collectmentioning
confidence: 99%
See 2 more Smart Citations